. Historical Analysis of Imam Sajjad's Strategies for Reviving Shiism after the Ashura Event Based on Diffusion Theory - Hamid reza Motahari; Mahmoud Bakhtiari (پژوهش های تاریخی)
Abstract Shiism experienced a significant crisis following the tragedy of Ashura characterized by oppression, fear, isolation, and the practice of taqiyyah. This study focused on the strategies employed by Imam Sajjad (A.S.) to revive Shiism in the aftermath of this event. Specifically, it addressed this question: How can we analyze Imam Sajjad’s strategies for revitalizing Shiism after the Ashura event? It appeared that Imam Sajjad (A.S.) utilized components of diffusion theory—namely, the destination of diffusion (environments that were both receptive and intolerant, along with political and cultural barriers), paths of diffusion (including displacement, contagious, and hierarchical diffusion), and timing of diffusion. By leveraging various tools, such as the community's reverence for the Prophet’s family, he transformed the emotional landscape created after Ashura, mitigating the effects of the oppressive Umayyad regime and countering the influence of pro-Umayyad scholars. Through initiatives like cadre building and promoting pilgrimage, he effectively revived Shiism after the Ashura event. This research elucidated Imam Sajjad's actions through the lens of diffusion theory, demonstrating how Shiism was revitalized in the wake of Ashura. Employing a historical methodology, the study analyzed Imam Sajjad's activities aimed at reviving Shiism, including cadre development, exposing Umayyad injustices, mobilizing the populace post-Karbala, challenging beliefs in predestination, elucidating the fundamental principles of Imamate, addressing key issues, and countering deviation through prayer and supplication.